2018
DOI: 10.1109/tpel.2017.2707581
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Switching Solid-State Transformer (S4T)

Abstract: My journey of doctoral study at Georgia Tech has never been short of amazing experiences and great challenges. Without the inspiration, support, and advice from many people, these challenges could never have been conquered and no milestones of the journey could have been reached. This thesis is a result of the many experiences that I gained from these people, to whom I would like to express my acknowledgements.First and foremost, I would like to extend my deepest gratitude to my advisor, Dr.Deepak Divan, for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…Considering simpler topologies or the use of resonant converters were suggested to improve efficiency [71]. As expected, a comparison between single and three-stage transformers conducted in [38] proved that single-stage SSTs are more efficient.…”
Section: Efficiency Of Solid State Transformersmentioning
confidence: 76%
“…Considering simpler topologies or the use of resonant converters were suggested to improve efficiency [71]. As expected, a comparison between single and three-stage transformers conducted in [38] proved that single-stage SSTs are more efficient.…”
Section: Efficiency Of Solid State Transformersmentioning
confidence: 76%
“…The bidirectional bridge arm of that kind of HF ac linked converter replaced by the IGBT in series with a diode or reverse-blocking IGBT, as called dynamic current (Dyna-C) topology [17], allows current to conduct in only one direction but blocks voltages in both directions. Soft-switching technique, high-power prototype design, and a class of partial resonant ac-link topology are developed [18]- [21]. The above matrix converter-type smart transformers mainly interface the three-phase ac with three-phase ac.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, the steady state model for PET has been proposed with considering the power loss characterization of VSC, and it can be applied to the AC/DC hybrid microgrids [7]. Recent research has demonstrated that the number of PET power conversion stage can be threestage, four-stage, and five-stage [8]- [10]. Furthermore, PET has a variety of circuit topologies, in which the low voltage AC and DC ports of mixed frequency modulation PET topology coupled together [11].…”
Section: Introductionmentioning
confidence: 99%